Meet the Expert : Wes McKinney on Scalable Python You Can Afford - McKinney, Wes (O'Reilly Media, Inc., 2021)
Join us for this edition of Meet the Expert with Apache Arrow cocreator Wes McKinney to learn considerations and best practices for distributed Python at scale-in a cost-effective way. You'll explore some of the computational systems challenges that go hand in hand with doing scalable distributed computing in Python and discover how working to improve data processing performance and efficiency in data science tools led Wes to help build the Apache Arrow project. What you'll learn and how you can apply it Understand common challenges in distributed computing Explore tools and practices for improving data processing performance and efficiency Discover cost-effective considerations for data processing at scale This course is for you because ... You want to learn about the fundamental shifts that are transforming the business landscape and customer needs. You want to overcome challenges that arise when working with large amounts of data. You want to discover new open source technologies and learn how to integrate them. Recommended follow-up: Read Python for Data Analysis, third edition (book)